Factors Affecting Impulsive Product and Service Buying Behavior: A Study of College Students in the Kathmandu Valley - Manandhar, Raju Bhai; Chalise, Mahananda; Poudel Bhusal, Namita; Adhikari, Ranjana; Manandhar, Eirika (International Research Journal of MMC, 2024)
Impulsive buying is the tendency of a customer to buy goods and services without planning. The study’s objective is to determine the factors affecting the impulsive buying behavior of the students in Kathmandu Valley. The study was based on the cross-sectional research design which followed the quantitative design. The study targeted college-level students studying at Bachelor’s and Master’s level in Kathmandu Valley. 200 students were selected from different colleges through a simple random sampling technique. A well-structured closed-ended survey questionnaire was developed and disseminated in a well-organized manner to respondents to collect the primary data from the field and analyzed systematically in 2023. The study analyzed the data using statistical tools like frequency distribution, mean, standard deviation, and correlation to derive the findings. The study finds that social influence is considered the first important cause influencing impulsive buying behavior. Similarly, it is followed by emotional triggers, lack of control, and financial resources influencing respectively. The study also shows that there was a strong relationship between social influence and impulse buying behavior. Business organizations should strategically leverage social factors in marketing campaigns to tap into this influential aspect of consumer behavior. Future researchers need to survey another variable with a large sample size by applying different methods.